The innovative school librarian - Bentley, Elizabeth; Pavey, Sarah; Sharper, Sue; Todd, Sally; Webb, Carol (Facet Publishing, 2016)
This book takes a strategic approach to the leadership of school libraries and will inspire and enable school librarians to think creatively about their work and the community in which they operate. The Innovative School Librarian raises important questions about the functions of the school librarian and sets out to encourage the reader to re-examine their own professional values, assumptions and practices. This has led to the inclusion of a new chapter on using evidence, a large number of new vignettes to illustrate responses to challenges as well as a significant re-structuring of other chapters. Written by current leaders in the field, each chapter addresses the practical issues facing school librarians. This new edition has been fully updated In the light of curriculum revisions, resource changes, developments in the use and integration of technology and new routes into the profession. Key topics covered include: * the librarian's philosophy and professional identity * bridging the gap between different visions for the school library * identifying and understanding our community * making a positive response to change * keeping inspired and inspiring others * integrating the library into teaching and learning. This is an essential, thought-provoking book for all school librarians, practitioners in schools library services, and students of librarianship. It has plenty to interest school leadership, headteachers, educational thinkers, public library managers and local government officers.--Provided by publisher.